A pragma-semiotic analysis of the Catholic bishops’ communiqué on the Ebola epidemic: Impact on the University of Ibadan Catholic faithful (2017)
This paper examines the extracts of the communiqué made by the Ibadan Catholic Bishops to the congregation on the Ebola epidemic. The paper identifies the practs, gives a semiotic interpretation of the signs visible, and discusses the impact of the communiqué on the Catholic faithful in the University of Ibadan, Nigeria. The data were collected from the Catholic Sunday Bulletin and the interviews conducted with, and the field notes collected from, the Catholic faithful informants (N=30) in the University of Ibadan. It utilised Mey’s pragmatic acts theory (PAT) and Saussure’s model of semiotic signs as the theoretical framework. The study shows that the communiqué is information motivated discourse on Ebola which comprises of direct acts that make use of the contextual features of shared situational knowledge, inferences, relevance, shared cultural knowledge, and references thereby exhibiting the pragmemes of cautioning, commanding, counselling and threatening; the semiotic sign ‘Holy Communion’ signifies the Body and Blood of Jesus Christ present in Bread and Wine, the semiotic sign ‘self-signing of oneself with holy water’ signifies spiritual cleansing, and the ‘sign of peace’ signifies love and unity among the people of God in the Church. Both the pragmemes and the semiotic signs have an impact on the Catholic Faithful in University of Ibadan.